Active homes that generate energy - Shatrova, I.; Belykh, V. (Ways to Improve Construction Efficiency, 2019)
This article outlines the problems of energy consumption and their solutions using technologies used in the construction of active houses with a positive energy balance. It reveals the concept of buildings that are combined with nature, which suggests that at home, being in balance with the outside world, should be as environmentally friendly and economical. The alternative energy sources are given, the most effective in the construction of such houses.